Mosques: Places of Education Outside of School - husarida; M Yahuda; Melia Jessica (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2023)
This research started from the background of the problem such as the lack of public understanding about the importance of Islamic religious education outside school, so this research discussed the use of the mosque which is used as a place for Islamic education outside of school (non-formal) at the Ar-Raudho mosque, Setiris Village, Marosebo District, Muaro Jambi Regency. The researcher focused this research on learning activities of the Qur'an in the Ar-Raudho mosque in Setiris Village, Marosebo District, Muaro Jambi Regency. This study aim to see the importance of the mosque as a place of education outside of school, especially Islamic religious education. This study used a qualitative descriptive method. The method of data collection was by conducting observations, interviews, and documentation. The data analysis technique was used by reducing the data, data presentation, and data conclusion drawing. The results of this study conclude that the Ar-Raudho mosque is used as an Al-Qur'an education place (TPQ) whose activities include recitations between Maghrib and Isha (PAMI) other than on Friday nights and Sunday nights. The Ar-Raudho Mosque is also used as a place to carry out all kinds of worship activities. The positive influence of the existence of TPQ in the Ar-raudho mosque is that it can prosper the mosque itself, increase religious knowledge for TPQ children, and shape the morals of children to be better, form religious, communicative, and independent characters. The results of this study conclude that the Ar-Raudho mosque is used as an Al-Qur'an education place (TPQ) whose activities include recitations between Maghrib and Isha (PAMI) other than on Friday nights and Sunday nights. The Ar-Raudho Mosque is also used as a place to carry out all kinds of worship activities. The positive influence of the existence of TPQ in the Ar-raudho mosque is that it can prosper the mosque itself, increase religious knowledge for TPQ children, and shape the morals of children to be better, form religious, communicative, and independent characters. The results of this study conclude that the Ar-Raudho mosque is used as an Al-Qur'an education place (TPQ) whose activities include recitations between Maghrib and Isha (PAMI) other than on Friday nights and Sunday nights. The Ar-Raudho Mosque is also used as a place to carry out all kinds of worship activities. The positive influence of the existence of TPQ in the Ar-raudho mosque is that it can prosper the mosque itself, increase religious knowledge for TPQ children, and shape the morals of children to be better, form religious, communicative, and independent characters. Keywords: Mosque, Islamic Education, Education Outside School